2018
DOI: 10.1186/s13046-018-0980-3
|View full text |Cite
|
Sign up to set email alerts
|

IMPDH2 promotes colorectal cancer progression through activation of the PI3K/AKT/mTOR and PI3K/AKT/FOXO1 signaling pathways

Abstract: BackgroundInosine 5′-monophosphate dehydrogenase type II (IMPDH2) was originally identified as an oncogene in several human cancers. However, the clinical significance and biological role of IMPDH2 remain poorly understood in colorectal cancer (CRC).MethodsQuantitative real-time polymerase chain reaction (qPCR), western blotting analysis, the Cancer Genome Atlas (TCGA) data mining and immunohistochemistry were employed to examine IMPDH2 expression in CRC cell lines and tissues. A series of in-vivo and in-vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(79 citation statements)
references
References 47 publications
2
77
0
Order By: Relevance
“…accelerated the migration and invasion of tumor cells. 31 Our present study also addressed the evidence that FNDC3B exerted positive effects on the activation of PI3K/mTOR signaling during promoting CRC cell processes. Contrarily, there was evidence suggested that mTOR inactivation could enhance cellular autophagy, which may be a protective measure for the survival of tumor cells.…”
Section: Discussionmentioning
confidence: 91%
“…accelerated the migration and invasion of tumor cells. 31 Our present study also addressed the evidence that FNDC3B exerted positive effects on the activation of PI3K/mTOR signaling during promoting CRC cell processes. Contrarily, there was evidence suggested that mTOR inactivation could enhance cellular autophagy, which may be a protective measure for the survival of tumor cells.…”
Section: Discussionmentioning
confidence: 91%
“…In the current study, we not only focused on the function of predicted target genes, but also combined the all genes of LUSC according to their correlation with miR‐486‐5p expression to understand the molecular functions. Among these function, the PI3K‐AKT signaling pathways, over activating in multiple cancers, was a central regulatory point in the process of cell proliferation, growth and differentiation, which was both predicted in GSEA and KEGG analysis . Moreover, we identified three important transcription factors (RUNX2, HOXD8, and HNF1A) that may influence significantly LUSC.…”
Section: Discussionmentioning
confidence: 80%
“…In human fibroblasts, inhibiting IMPDH via MPA treatment was shown to lead to decreased adhesion and migration along with dysregulated cytoskeletal proteins (65). Similarly, MPA treatment led to a decrease in the migration and invasion of gastric cancer cells in vitro (66) and to a decrease in the EMT, in vitro migration, and metastatic seeding of prostate cancer cells (67). IMPDH inhibition was reported to decrease the fraction of GTP-bound RAC1, RHOA, and RHOC, the molecular switch proteins responsible for polarizing cells during migration (68), in melanoma cells (69).…”
Section: Gtp Biosynthetic Enzymes In Cancer Cell Dissemination Impdhmentioning
confidence: 96%